2018
DOI: 10.1038/s41598-017-19013-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on the gut microbiota of high fat diet-induced hypercholesterolemic rats

Abstract: The aim of the present study was to investigate alterations in gut microbiota associated with hypercholesterolemia and treatment with atorvastatin, a commonly prescribed cholesterol-lowering drug. In this study, seven experimental groups of rats were developed based on diets [high-fat diet (HFD) and normal chow diet (NCD)] and various doses of atorvastatin in HFD and NCD groups. 16S rRNA amplicon sequencing was used to analyze the gut microbiota. Atorvastatin significantly reduced the cholesterol level in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 52 publications
11
78
1
2
Order By: Relevance
“…The genus Helicobacter, a potential producer of intracellular reactive oxygen species and MDA, induces gastric inflammation and gastrointestinal infection [37,38]. Moreover, an elevated abundance of Clostridium and SMB53 due to an HFD was in agreement with a previous report [39].…”
Section: Discussionsupporting
confidence: 90%
“…The genus Helicobacter, a potential producer of intracellular reactive oxygen species and MDA, induces gastric inflammation and gastrointestinal infection [37,38]. Moreover, an elevated abundance of Clostridium and SMB53 due to an HFD was in agreement with a previous report [39].…”
Section: Discussionsupporting
confidence: 90%
“…Ruminococcus is a genus reversed uniquely by ATO and its reversion by ATO was also reported in a previous study. 15 Lower levels of Ruminococcus are associated with higher levels of CRP and IL-6. However, another study found that the abundance of Rumicoccus gnavus was higher in ACDV patients compared with controls.…”
Section: Discussionmentioning
confidence: 98%
“…The dose of administration of ATO and strains were determined by referring to previous studies and was verified by preliminary experiments. 6,15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between exercise and vitamin D status with statin use warrant further study. Increased research is also needed into the gut microbiome, as it has recently been shown to be significantly perturbed by statins [278,279] and might module statin response [280]. Much has been done; much work remains.…”
Section: Discussionmentioning
confidence: 99%